A Measure of Capital - Pyatt, Graham (Review of Economic Studies, 1963)
Journal Article A Measure of Capital Get access Graham Pyatt Graham Pyatt Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 3, October 1963, Pages 195–202, https://doi.org/10.2307/2296320 Published: 01 October 1963